MERGER OF BANK MUAMALAT AND BANK BTN SYARI'AH (MASLAHAH MURSALAH PERSPECTIVE) - Tasya Anjani; Dedi Sunardi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Backgrounds: It is believed that Bank Muamalat Indonesia's merger policy with Bank BTN Syari'ah can strengthen the market share of the two banks themselves, where Bank BTN focuses on subsidized home financing in collaboration with Bank Muamalat Indonesia which focuses on retail financing. Objectives Therefore, this research aims to analyze the merger policy of Bank Muamalat Indonesia with Bank BTN Syari'ah Indonesia from the maslahah murlah perspective. Methods: This research is qualitative research with a descriptive approach, namely describing the advantages and disadvantages of the merger of Bank Muamalat Indonesia with BTN Syari'ah Indonesia. The data used in this research is secondary data that researchers obtained from books, scientific journals, magazines, newspapers and various other credible sources. These data were analyzed using the stages of data collection, data reduction, data selection, and drawing conclusionstool. Results and Conclusions: the merger of Bank Muamalat Indonesia and BTN Syari'ah Indonesia is in line with the principle of maslahah murlah, namely to bring benefits, goodness and avoid damage in terms of increasing the sharia banking market share, increasing Bank Muamalat's assets. and BTN Syari'ah, and increasing strength in achieving surplus due to collaboration in subsidized housing financing and retail financing between Bank Muamallat and Bank BTN Syari'ah.